Analisis Simulasi Tegangan Punch dan Die pada Blanking untuk Produk Dudukan Handphone - Annisa Syabina; Idiar Idiar; Sugianto Sugianto (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to design a blanking die used for mass-producing mobile phone holders while prioritizing efficiency and dimensional accuracy. The die set developed includes key components such as the punch, die, stripper, guide post, and fastening bolts. The product produced has dimensions of 138 × 63 × 2 mm and uses ST 37 steel as the raw material. Based on calculations, the required blanking force is 129,000 kN, which is considered safe for the production process. The design also accounts for an optimal clearance of 0.083 mm and a die thickness of 35 mm to effectively withstand the working load. Simulations using stress analysis methods reveal that the von Mises stress distribution on both the punch and die remains below the elastic limit of SKD11 material. The maximum stress on the punch is recorded at 2.437 × 10⁵ N/m², while on the die it reaches 5.153 × 10⁵ N/m², both well below the yield strength of SKD11, which is 2.918 × 10⁸ N/m², indicating that these components operate safely without the risk of plastic deformation. To strengthen the construction, the stripper is designed with a thickness of 12 mm, and the addition of four SCM435 bolts is recommended to improve system stability. This die design is verified through manual calculations and Finite Element Analysis (FEA) to ensure its reliability. Overall, the findings of this study demonstrate that the designed blanking die can support mass production with high precision, optimal structural strength, and long-term durability.